Gambaran Menarche pada Remaja Siswi di Sekolah Menengah Pertama Negeri-14 Palangka Raya: Description of Menarche in Adolescent Students at Junior High School 4 Palangka Raya - Chrisdianti Yulita; Ivana Devitasari; Merry Delika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Adolescence is a transition period from childhood to adulthood marked by accelerated physical, mental, emotional, and social development and takes place in the second decade of life. Adolescence is marked by puberty, which is when a girl can experience conception, namely menarche / first menstruation. Menarche is a biological characteristic of female sexual maturity that generally occurs at about 10-14 years old. Objective: To discover the description of menarche in adolescent girls at SMPN-14 Palangka Raya. Method: This study uses a descriptive design, which is research conducted with the main objective of making a description or descriptive. This study used a saturated sampling method with a total of 39 female adolescent respondents who had experienced menarche, and the technique of collecting data was using a questionnaire. Result: The most age in adolescents who experienced menarche at 11-14 years were 37 people (94.8%), with normal BMI as many as 20 respondents (51.3%), adolescent girls exposed to adult information media, and as many as 25 respondents. (64.1%), the highest number of mothers education for students who had menarche was in basic education, 20 respondents (51.3%), with mothers who did not work as many as 23 people (59%), and high family incomes ((≥Rp.1,676 .058,-/month) as many as 20 respondents (51.3%). Conclusion: Menarche in adolescents aged 11-14 years occurs not only due to endogenous (genetic) factors but also exogenous factors, namely nutritional status, exposure to adult media, both print and electronic, sports activities, socioeconomic status, and education level of parents. as the closest person to the teenager.